2015
DOI: 10.1016/j.neuropharm.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ghrelin antagonists on alcohol drinking and reinforcement in mouse and rat models of alcohol dependence

Abstract: An effort has been mounted to understand the mechanisms of alcohol dependence in a way that may allow for greater efficacy in treatment. It has long been suggested that drugs of abuse seize fundamental reward pathways and disrupt homeostasis to produce compulsive drug seeking behaviors. Ghrelin, an endogenous hormone that affects hunger state and release of growth hormone, has been shown to increased alcohol intake following administration, while antagonists decrease intake. Using rodent models of dependence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 42 publications
4
29
0
Order By: Relevance
“…Alcohol does not have an identified specific neurotransmitter binding site, but ethanol receptive elements within the membrane may provide a sensitive site for ethanol actions (Tabakoff and Hoffman, 1992). Preclinical studies have identified several neuromodulatory systems that are modulated by ethanol and that represent potential targets for future medications (De Witte et al, 2005;Spanagel and Kiefer, 2008;Tanchuck et al, 2011;Funk et al, 2007;Gehlert et al, 2007;Valdez and Koob, 2004;Nealey et al, 2011;Walker et al, 2011;de Guglielmo et al, 2015;Martin-Fardon et al, 2010;Logrip et al, 2015;King et al, 2017;Gomez et al, 2015;Franklin et al, 2015;Hu et al, 2011;Logrip et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol does not have an identified specific neurotransmitter binding site, but ethanol receptive elements within the membrane may provide a sensitive site for ethanol actions (Tabakoff and Hoffman, 1992). Preclinical studies have identified several neuromodulatory systems that are modulated by ethanol and that represent potential targets for future medications (De Witte et al, 2005;Spanagel and Kiefer, 2008;Tanchuck et al, 2011;Funk et al, 2007;Gehlert et al, 2007;Valdez and Koob, 2004;Nealey et al, 2011;Walker et al, 2011;de Guglielmo et al, 2015;Martin-Fardon et al, 2010;Logrip et al, 2015;King et al, 2017;Gomez et al, 2015;Franklin et al, 2015;Hu et al, 2011;Logrip et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For each week of CIE vapor or control air exposure, mice were placed into hanging wire mesh cages inside inhalation chambers (Flair Plastics, Portland, OR) that were housed inside climate‐controlled chambers (Weaver Technologies, Portland, OR). CIE or control exposure to intermittent EtOH vapor or air occurred over 3 days (17 h/d × 3 days; Table ), using routine procedures (Finn et al., ; Gomez et al., ). Food and water were freely available.…”
Section: Methodsmentioning
confidence: 99%
“…As withdrawal severity has been used as an index of physical dependence in rodent models, the results suggested that repeated bouts of CIE vapor exposure produce physical dependence. Importantly, CIE vapor exposure has been shown to be a useful behavioral model of the escalation of EtOH consumption in dependent animals, and it has been used by many investigators to test pharmacological targets for their ability to decrease high EtOH consumption in dependent rodents (Bell et al., ; Finn et al., ; Gomez et al., ; Nealey et al., ; Richardson et al., ; Roberts et al., ; Suchankova et al., ; Walker and Koob, ; Walker et al., ).…”
mentioning
confidence: 99%
“…Ghrelin has also been implicated in reward-related behaviors and, more specifically, in the modulation of food intake and reward (Dickson et al 2011). Additionally, preclinical work has shown that ghrelin may play a role in alcohol reward and consumption, and that ghrelin receptor antagonism blocks these behaviors (Gomez et al 2015; Gomez & Ryabinin 2014; Jerlhag et al 2009; Kaur & Ryabinin 2010; Landgren et al 2012; Stevenson et al 2015; Suchankova et al 2013). Consistent with this preclinical work, clinical studies have reported changes in blood ghrelin levels in alcoholic patients versus controls and a positive correlation between blood levels of ghrelin and alcohol craving (Addolorato et al 2006; Badaoui et al 2008; Koopmann et al 2012; Leggio et al 2012).…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%